Earthquake stress via event ratio levels: Application to the 2011 and 2016 Oklahoma seismic sequences - William R. Walter; Seung‐Hoon Yoo; Kevin Mayeda; Rengin Gök (Geophysical Research Letters)
Abstract We develop a new methodology for determining earthquake stress drop and apparent stress values via spectral ratio asymptotic levels. With sufficient bandwidth, the stress ratio for a pair of events can be directly related to these low‐ and high‐frequency levels. This avoids the need to assume a particular spectral model and derive stress drop from cubed corner frequency measures. The method can be applied to spectral ratios for any pair of closely related earthquakes and is particularly well suited for coda envelope methods that provide good azimuthally averaged, point‐source measures. We apply the new method to the 2011 Prague and 2016 Pawnee earthquake sequences in Oklahoma. The sequences show stress scaling with size and depth, with the largest events having apparent stress levels near 1 MPa and smaller and/or shallower events having systematically lower stress values.